Effectiveness of Bacteria Isolated from Peat Swamp Forests to Control Rice Dirty Panicle Fungi in Thailand - Unartngam, Jintana; Naunnet, Thiphaphorn; Sangsuk, Sasawat; Chountragoon, Orawan; Kerdkhong, Chommanat; Tantirungkij, Manee (AGRIVITA, Journal of Agricultural Science, 2021)
Rice dirty panicle disease is one of the most important problems in Thailand. The fungal pathogens were reported to be many species including Curvularia lunata, Bipolaris oryzae, Fusarium incarnatum, Sarocladium oryzae, Trichoconis padwickii and Cercospora oryzae. Biological control is an alternative method for controlling this disease and reducing the application of fungicides. Therefore, this study aimed to evaluate the antagonistic potential of bacteria isolated from peat swamp forests in Thailand. A total of 513 bacterial isolates were collected and screened in the laboratory using the dual culture method. The results revealed that three of the 513 bacterial strains (IBK-4, IBK-8 and IBK-5) were highly inhibitory to the fungal pathogens including C. lunata, B. oryzae and F. incarnatum. These three strains were identified as Bacillus (IBK-4 and IBK-8) and Brevibacillus (IBK-5) based on 16S rRNA sequencing. Then, these three strains were evaluated on a susceptible rice variety by inoculation with three fungal pathogens. The results indicated that Bacillus strain IBK-8 had the highest efficiency to control the disease development as observed in the disease severity and index. The results of this study indicated that bacterial strains from peat swamp forests have the potential to be antagonistic to plant pathogens.